Pengembangan Budaya Literasi Dalam Pembelajaran Tematik Integratif Di Madrasah Ibtidaiyah - Jamilatun Nafi’ah (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Literacy plays an important role in learning including at the elementary school level. Literate ability is good for students, encouraging the development of other abilities, because literacy is a basic ability to gain abilities in other fields. Especially in providing an understanding of the 2013 thematic integrative curriculum learning. Learning that contains several subject matters integrated into one theme needs to empower literacy culture in its application. Literacy culture in integrative thematic learning can be developed in terms of classroom management, choosing learning methods related to literacy and choosing strategies in applying literacy to integrative thematic learning.